Serendipitous Discovery of Lipemia Retinalis in a Premature Infant: A Case Report - Homayoun Nikkhah; Narges Karrabi; Ehsan Yazdani; Rezvan Nezameslami (Case Reports in Ophthalmology)
Introduction: Lipemia retinalis (LR) is a rare ocular condition characterized by a creamy white appearance of the retinal vessels, which is indicative of significantly elevated serum triglyceride (TG) levels. This condition is particularly noteworthy in pediatric populations, especially in preterm infants who are at risk for various metabolic disorders. Case Presentation: We report a case of LR in a 44-day-old preterm infant identified during routine retinopathy of prematurity (ROP) screening. Unusual retinal findings led to metabolic investigations, revealing elevated TG levels confirming LR. The infant was managed with a dietary regimen including skimmed milk, resulting in a substantial decrease in TG levels and complete resolution of the retinal changes. Conclusion: Fundus examination serves as a portal to the systemic health of an individual, enabling rare identification of LR, indicative of underlying dyslipidemia. This case underscores the necessity for comprehensive metabolic screening in preterm infants, particularly during ROP assessments. Furthermore, it emphasizes the effectiveness of dietary interventions in managing LR. The favorable outcomes stress the significance of early detection of LR in pediatric patients and implementing nutritional strategies to enhance metabolic well-being, thereby averting severe hypertriglyceridemia complications.